Elucidation of factors shaping reactivity of 5'-deoxyadenosyl - a prominent organic radical in biology - Wojdyla, Zuzanna; Maldonado-Domínguez, Mauricio; Bharadwaz, Priyam; Culka, Martin; Srnec, Martin (Physical chemistry chemical physics : PCCP, 2024)
This study investigates the factors modulating the reactivity of 5'-deoxyadenosyl (5'dAdo ̇) radical, a potent hydrogen atom abstractor that forms in the active sites of radical SAM enzymes and that otherwise undergoes a rapid self-decay in aqueous solution. Here, we compare hydrogen atom abstraction (HAA) reactions between native substrates of radical SAM enzymes and 5'dAdo ̇ in aqueous solution and in two enzymatic microenvironments. With that we reveal that HAA efficiency of 5'dAdo ̇ is due to (i) the in situ formation of 5'dAdo ̇ in a pre-ordered complex with a substrate, which attenuates the unfavorable effect of substrate:5'dAdo ̇ complex formation, and (ii) the prevention of the conformational changes associated with self-decay by a tight active-site cavity. The enzymatic cavity, however, does not have a strong effect on the HAA activity of 5'dAdo ̇. Thus, we performed an analysis of in-water HAA performed by 5'dAdo ̇ based on a three-component thermodynamic model incorporating the diagonal effect of the free energy of reaction, and the off-diagonal effect of asynchronicity and frustration. To this aim, we took advantage of the straightforward relationship between the off-diagonal thermodynamic effects and the electronic-structure descriptor - the redistribution of charge between the reactants during the reaction. It allows to access HAA-competent redox and acidobasic properties of 5'dAdo ̇ that are otherwise unavailable due to its instability upon one-electron reduction and protonation. The results show that all reactions feature a favourable thermodynamic driving force and tunneling, the latter of which lowers systematically barriers by ∼2 kcal mol-1. In addition, most of the reactions experience a favourable off-diagonal thermodynamic contribution. In HAA reactions, 5'dAdo ̇ acts as a weak oxidant as well as a base, also 5'dAdo ̇-promoted HAA reactions proceed with a quite low degree of asynchronicity of proton and electron transfer. Finally, the study elucidates the crucial and dual role of asynchronicity. It directly lowers the barrier as a part of the off-diagonal thermodynamic contribution, but also indirectly increases the non-thermodynamic part of the barrier by presumably controlling the adiabatic coupling between proton and electron transfer. The latter signals that the reaction proceeds as a hydrogen atom transfer rather than a proton-coupled electron transfer.
Keywords: S-Adenosylmethionine; Deoxyadenosines; termodynamika; Catalytic Domain; Water; deoxyadenosiny; Thermodynamics; Free Radicals; katalytická doména; volné radikály; voda; S-adenosylmethionin; Hydrogen; vodík